Libraries and librarians in a future world (Confluenţe Bibliologice, 2018)
In the period of the 31st October extended till the 10th of November 2018, Mihaela Staver with five colleagues from the libraries of the Higher Education Institutions of the Republic of Moldova has lived an unprecedented professional experience in university libraries in North Carolina, USA, as well as in the Washington Congress Library, as a participant in the Open World program, a program supported by the US Embassy in the Republic of Moldova.
Keywords: international projects; informational resources